Highlights of the IFPRI and WFP partnership: Working together to ensure food and nutrition security - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
More than two decades of strong partnership between the World Food Programme (WFP) and the International Food Policy Research Institute (IFPRI) began with a shared goal of creating more effective and efficient food aid distribution systems. Our work helped improve the delivery of essential food aid to the most vulnerable in times of crisis, inform decisions to administer food or cash transfers using sound evidence, and strengthen evidence-based policy making by developing information systems and networks for food security. Over time, the collaboration moved toward designing social protection programs that use food and cash transfers to improve nutrition for the poor. More recently, our partnership has contributed to helping vulnerable people become more resilient to shocks and crises and to moving countries toward pathways of long-term growth, prosperity, and Zero Hunger. This brochure presents highlights of the IFPRI-WFP partnership.